FUNCTIONAL CAPACITY OF PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE UNDERGOING REHABILITATION PROGRAMS: AN INTEGRATIVE REVIEW (CIPEEX, 2025)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) is a progressive condition caused by airway obstruction, often resulting from exposure to harmful particles. COPD is one of the leading causes of global mortality, and although it has no cure, pulmonary rehabilitation (PR) can be an effective alternative to control the disease and improve patients’ quality of life. PR involves physical training, education, and behavioral changes. Objective: To analyze the effects of PR on improving pulmonary functional status in patients with COPD. Methodology: Eight original articles in English published between 2015 and 2024 were selected from PubMed using the Health Sciences Descriptors “chronic obstructive pulmonary disease,” “pulmonary rehabilitation,” “functional status,” and “quality of life,” combined with the Boolean operator “AND.” Inclusion criteria were studies that used the Six-Minute Walk Test (6MWT) and the Incremental Shuttle Walk Test (ISWT) to assess functional status. Results: The studies analyzed showed that PR significantly improves functional status in COPD patients, as evidenced by 6MWT and ISWT performance. PR was associated with increased walking distances and improved patient quality of life. Conclusion: Pulmonary rehabilitation is effective in enhancing exercise capacity and functional status in COPD patients. Although the studies show significant benefits, further research is needed to evaluate long-term effects and confirm PR’s efficacy.
Keywords: Chronic obstructive pulmonary disease; Pulmonary rehabilitation; Health-related quality of life